2016
DOI: 10.1186/s13063-016-1452-8
|View full text |Cite
|
Sign up to set email alerts
|

A parenting programme to prevent abuse of adolescents in South Africa: study protocol for a randomised controlled trial

Abstract: BackgroundAn estimated one billion children experience child abuse each year, with the highest rates in low- and middle-income countries. The Sinovuyo Teen programme is part of Parenting for Lifelong Health, a WHO/UNICEF initiative to develop and test violence-prevention programmes for implementation in low-resource contexts. The objectives of this parenting support programme are to prevent the abuse of adolescents, improve parenting and reduce adolescent behavioural problems. This trial aims to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…For the more sensitive questions, tablets with Audio Computer‐Assisted Self‐Interview Software (ACASI) options were available. Further information about the Sinovuyo Teen trial recruitment, design, and methods can be found in the trial protocol (Cluver et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…For the more sensitive questions, tablets with Audio Computer‐Assisted Self‐Interview Software (ACASI) options were available. Further information about the Sinovuyo Teen trial recruitment, design, and methods can be found in the trial protocol (Cluver et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The control arm clusters received a hygiene information event. More details, including power calculations for the trial, are available in the study protocol (Cluver et al 2016b).…”
Section: Participantsmentioning
confidence: 99%
“…Given the dearth of appropriate evidence-based family interventions in South Africa (Wessels, 2012) and in low-and middle-income countries (Mejia Calam, & Sanders, 2012), organisations are more likely to rely on international interventions that have been rigorously evaluated in high-income countries (Cluver et al, 2016). Noting the real dangers of using unadapted Western models of intervention (Mejia, Leijten, Lachman, & Parra-Cardona, 2017), and unthinkingly reinforcing gendered norms of caregiving (Molyneux, Jones, & Samuels, 2016), caution needs to be exercised in uncritically transposing these programmes in different countries with different cultural beliefs about families and caregiving and different resource levels.…”
Section: Discussionmentioning
confidence: 99%